Adsorption Kinetics of Cd(II) From Aqueous Solution Using Surfactant Modified Activated Carbon-Sodium Lauryl Sulphate (SMAC-SLS) - Side, Sumiati; Putri, Suriati Eka; Perdana, Rini; Rahman, Abd. (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2024)
The purpose of this study was to determine the adsorption kinetic model of Cd(II) from aqueous solution using Surfactant Modified Activated Carbon-Sodium Lauryl Sulphate (SMAC-SLS). This study began by varying pH, contact time, and adsorbate concentration. The concentration of Cd(II) was measured using a spectrophotometric method. The results of the analysis showed that the optimum pH occurred at pH 5 with an adsorption percentage of 84.58±1.44% and the optimum contact time at 100 minutes with an adsorption percentage of 88.75±1.5%. Furthermore, in the variation of adsorbate concentration, the adsorption percentage decreased with increasing adsorbate concentration. The adsorption kinetics followed a pseudo second order with an R2 value of 0.9945 with an adsorption capacity of 8.89 mg/g. Thus, the use of SMAC-SLS as a future adsorbent for Cd(II) is highly recommended.